Hydrogen Cyanide in the Rhizosphere: Not Suppressing Plant Pathogens, but Rather Regulating Availability of Phosphate - Rijavec, Tomaž; Lapanje, Aleš (Frontiers in Microbiology, 2016)
Plant growth promoting rhizobacteria produce chemical compounds with different benefits for the plant. Among them, HCN is recognized as a biocontrol agent, based on its ascribed toxicity against plant pathogens. Based on several past studies questioning the validity of this hypothesis, we have re-addressed the issue by designing a new set of in vitro experiments, to test if HCN-producing rhizobacteria could inhibit the growth of phytopathogens. The level of HCN produced by the rhizobacteria in vitro does not correlate with the observed biocontrol effects, thus disproving the biocontrol hypothesis. We developed a new concept, in which HCN does not act as a biocontrol agent, but rather is involved in geochemical processes in the substrate (e.g. chelation of metals), indirectly increasing the availability of phosphate. Since this scenario can be important for the pioneer plants living in oligotrophic alpine environments, we inoculated HCN producing bacteria into sterile mineral sand together with germinating plants and showed that the growth of the pioneer plant French sorrel was increased on granite-based substrate. No such effect could be observed for maize, where plantlets depend on the nutrients stored in the endosperm. To support our concept, we used KCN and mineral sand and showed that mineral mobilization and phosphate release could be caused by cyanide in vitro. We propose that in oligotrophic alpine environments, and possibly elsewhere, the main contribution of HCN is in the sequestration of metals and the consequential indirect increase of nutrient availability, which is beneficial for the rhizobacteria and their plant hosts.